Dimensions that Make Up the Exclusion Risk in the Transportation System in the City of Cali, Colombia - Mosquera Abadia, Henry A. (Cuadernos de Administración, 2015)
Informal transportation systems have become the way to guide the population’s unmet transportation needs. It has been found that a strong relationship exists between labor informality and situations of social exclusion related to the use of informal transportation systems. This situation brings, as a consequence, higher costs to the formal transportation system in the cities. Hence, this article sought to identify the dimensions that constitute the risk of exclusion in transportation for the users of the Occidental Mass Integrated Transport system (MIO, for the term in Spanish) of the city of Cali, Colombia, and the risk in which it is found in relation to the transportation service, elements of fundamental importance for decision makers in the city. To assess exclusion in the MIO system, five dimensions were used that indicate the probability of risk of social exclusion (SOCEX) of a person, like family income, economic activity, political activity, social participation and support